(untitled) (Annals of Medical Research, 2023)
Aim: In this study, we aimed to examine the factors predicting pregnancy by comparing successful in vitro fertilization/ intracytoplasmic sperm injection (IVF)/(ICSI) fresh cycles with previous failed ones of the same patients in the same year. Materials and Methods: The study consisted of two groups, failed (n:283) and successful IVF fresh cycles (n:283) that applied one after another within the same year, thusly each woman acted under her own control. IVF treatment indications, antral follicle count, ovulation induction protocol type, initial and total gonadotropin dose, progesterone, and estradiol (E2) levels on the trigger day, the number of oocytes retrieved and mature oocytes, number of Grade 1, Grade 2, Grade 3 embryo, day of embryo transfer (ET), endometrial thickness on trigger and oocyte pick-up (OPU) day, embryo-fundus distance and beta-human chorionic gonadotropin (B-hCG) levels on the 10th day after the ET were measured. The same luteal phase support was administered in both groups. Results: Totally 566 cycles and 283 women were included in the study. There was a significant difference in luteinizing hormone (LH) levels on OPU day and number of grade 1 ET between the two groups, LH levels on OPU day and number of grade 1 ET were higher in successful IVF fresh cycles group (p<0.05). Conclusion: Low serum LH levels on OPU day was associated with decreased pregnancy results. Increased IVF success was observed in grade 1 ET cycles.